Capillary hydrodynamic fractionation of hydrophobic colloids: errors in the estimated particle size distribution - Vega, Jorge Rubén (2013)
Capillary hydrodynamic fractionation (CHDF) with turbidity detection at a single wavelength is an analytical technique that is often used for sizing the submicrometric particles of hydrophobic colloids. This article investigates three sources of errors that affect the particle size distribution (PSD) estimated by CHDF: diameter calibration errors, uncertainties in the particle refractive index (PRI), and instrumental broadening (IB). The study is based on simulated and experimental examples that involve unimodal and bimodal PSDs. Small errors in the diameter calibration curve can produce important deviations in the number average diameter due to systematic shifts suffered by the PSD modes. Moderate uncertainties in the PRI are unimportant in the analysis of unimodal PSDs, but in the specific case of bimodal PSDs, errors in the PRI can strongly affect the estimated number concentration of each mode. The typical IB correction (based on the IB function estimated from narrow standards) produces slightly erroneous average diameters but can lead to PSDs with underestimated widths and distorted shapes. In practice, the three investigated sources of errors can be present simultaneously, and uncertainties in the average diameters, the shape and width of the PSD, and the number concentration of the PSD modes are unavoidable.